2020
DOI: 10.2166/washdev.2020.112
|View full text |Cite
|
Sign up to set email alerts
|

Sources of microbiological contamination in sachet water from Ghana

Abstract: Abstract Sachet water is one of the primary sources of drinking water in rapidly growing countries. A study to assess the microbiological quality of sachet water in 21 different brands was conducted in Ghana. Culturable total coliform was positive in 87% of the samples collected, where Escherichia coli colonies were absent. The analysis of quantitative polymerase chain reaction results indicated the presence of E. coli genes in 44.6% of the samples, with the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is underground water that has been further treated and is thus considered safe. Nevertheless, both physico-chemical and bacterial contamination in sachet water have been reported in Ghana [45,46]. The present study did not assess physicochemical and bacterial contamination of drinking water either from the source or from storage containers.…”
Section: Plos Watermentioning
confidence: 84%
“…It is underground water that has been further treated and is thus considered safe. Nevertheless, both physico-chemical and bacterial contamination in sachet water have been reported in Ghana [45,46]. The present study did not assess physicochemical and bacterial contamination of drinking water either from the source or from storage containers.…”
Section: Plos Watermentioning
confidence: 84%
“…Earlier studies in Ghana and Nigeria have variously indicated sachet water to be contaminated with faecal coliform and other pathogenic bacteria and not wholesome [29][30][31]. Semey, Dotse-Gborgbortsi [32] explained in their study that the contamination might be due to the unhygienic handling by factory workers during production.…”
Section: Discussionmentioning
confidence: 95%
“…Dzodzomenyo, Fink [33] have further indicated that some of the sachet water companies are not formally registered by the Food and Drug Authority and might be violating the guidelines of the standard for quality water production. It is therefore not surprising that Aslan, Rochani [29] study which examined the sachet bag observed some bags not to have a batch number, date of manufacture and no information on treatment. This is worrisome as the shift to drinking sachet water might not necessarily be protective against cholera.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) reported that at least two billion people drink fecal-contaminated water containing pathogens, associated with 485,000 diarrheal deaths each year, most of them infants (WHO 2019). These health hazards posed by pathogen-contaminated water are severe, especially in rural areas of developing countries (WHO 2019); even commercial sachet water sometimes contains pathogens (Aslan et al 2021).…”
Section: Introductionmentioning
confidence: 99%